How Much Is Enough in a Perfect World? Cultural Variation in Ideal Levels of Happiness, Pleasure, Freedom, Health, Self-Esteem, Longevity, and Intelligence. (September 2018) - Hornsey, Matthew J.; Bain, Paul G.; Harris, Emily A.; Lebedeva, Nadezhda; Kashima, Emiko S.; Guan, Yanjun; González, Roberto; Chen, Sylvia Xiaohua; Blumen, Sheyla
The maximization principle—that people aspire to the highest possible level of something good if all practical constraints are removed—is a common yet untested assumption about human nature. We predict that in holistic cultures—where contradiction, change, and context are emphasized—ideal states of being for the self will be more moderate than in other cultures. In two studies ( N s = 2, 392 and 6, 239), we asked this question: If participants could choose their ideal level of happiness, pleasure, freedom, health, self-esteem, longevity, and intelligence, what level would they choose? Consistent with predictions, results showed that maximization was less pronounced in holistic cultures; members of holistic cultures aspired to less happiness, pleasure, freedom, health, self-esteem, longevity, and IQ than did members of other cultures. In contrast, no differences emerged on ideals for society. The studies show that the maximization principle is not a universal aspect of human nature and that there are predictable cultural differences in people's notions of perfection.